2014
DOI: 10.4311/2012es0284
|View full text |Cite
|
Sign up to set email alerts
|

The Mineralogical Study of the Grotta Inferiore di Sant'Angelo (Southern Italy)

Abstract: In the present work, thirteen samples collected from the Grotta Inferiore di Sant'Angelo near the town of Cassano allo Jonio (Calabria region, southern Italy) were analyzed for their mineralogy. The Grotta Inferiore di Sant'Angelo is made up of subhorizontal, interlinked galleries between 400 and 450 meters above sea level. The floor is littered with deposits such as bat-guano, gypsum, and many speleothems that also cover the walls. The samples were identified and characterized by X-ray powder diffraction, sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…14), as is replacement gypsum, which was even quarried in the past. In addition to gypsum and detrital minerals, mineralogical studies found deposits of thin globular concretions and crystals of barite on corrosional pockets, and thin films of halite or rare sylvite crystals coating the gypsum (Catalano et al 2014).…”
Section: North Calabriamentioning
confidence: 99%
“…14), as is replacement gypsum, which was even quarried in the past. In addition to gypsum and detrital minerals, mineralogical studies found deposits of thin globular concretions and crystals of barite on corrosional pockets, and thin films of halite or rare sylvite crystals coating the gypsum (Catalano et al 2014).…”
Section: North Calabriamentioning
confidence: 99%